The Effect of Delayed Reporting on Mock-Juror Decision-Making in the Era of #MeToo. Issue 13 (July 2022) - Fraser, Bailey M.; Pica, Emily; Pozzulo, Joanna D.
The #MeToo movement has given voice to victims of sexual harassment and assault. In many of these cases, there have been long delays in reporting of the sexual offence (e.g., the Harvey Weinstein case). The purpose of this study was to examine how the type of sexual offence (harassment vs. assault) and the length of delayed reporting (15, 25, 35 years) influenced mock-juror decision-making. Mock-jurors ( N = 319) read a mock trial transcript depicting an alleged sexual offence and were asked to render a dichotomous verdict, continuous guilt rating, and defendant and victim perception ratings. The data indicated an effect of sexual offence type such that mock-jurors held more favorable perceptions of the defendant when the alleged offence was harassment compared with assault. There also was an effect of delayed reporting such that mock-jurors rendered more guilty verdicts when there was a 25-year delay compared with a 15-year delay. Intriguingly, these results suggest that jurors in sexual offence cases may perceive longer delays in reporting as more believable than shorter delays.